2020
DOI: 10.1101/2020.02.19.952366
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multi-omic surveillance of Escherichia coli and Klebsiella spp. in hospital sink drains and patients

Abstract: Escherichia coli and Klebsiella spp. are important human pathogens that cause a wide spectrum of clinical disease. In healthcare settings, sinks and other wastewater sites have been shown to be reservoirs of antimicrobial-resistant E. coli and Klebsiella spp., particularly in the context of outbreaks of resistant strains amongst patients. Without focusing exclusively on resistance markers or a clinical outbreak, we demonstrate that many hospital sink drains are abundantly and persistently colonised with divers… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…This multispecies biofilm-mediated tolerance to biofilms is something we have observed previously (35), but it would require a different study protocol to evidence clearly in the sink trap biofilm model. We equally recognize that the biofilm populations of different sink traps are not likely to be entirely consistent with each other, as evidenced by a recent publication (36), especially given different experimental conditions, but found that there was consistent isolation in the trap of P. aeruginosa and Enterobacter and Citrobacter that allowed a degree comparison both analyzed.…”
Section: Discussionmentioning
confidence: 85%
“…This multispecies biofilm-mediated tolerance to biofilms is something we have observed previously (35), but it would require a different study protocol to evidence clearly in the sink trap biofilm model. We equally recognize that the biofilm populations of different sink traps are not likely to be entirely consistent with each other, as evidenced by a recent publication (36), especially given different experimental conditions, but found that there was consistent isolation in the trap of P. aeruginosa and Enterobacter and Citrobacter that allowed a degree comparison both analyzed.…”
Section: Discussionmentioning
confidence: 85%